Performance evaluation of lateritic subgrade soil treated with lime and coir fibre-activated carbon - Tamassoki, Sakina; Nik Daud, Nik Norsyahariati; Mohd Jakarni, Fauzan; Mohd Kusin, Faradiella; A. Rashid, Ahmad Safuan; Roshan, Mohammad Jawed (MDPI, 2022)
The subgrade layer’s stability considerably influences the long-term performance of pavement systems. This study investigates the influence of lime as a traditional stabiliser and activated carbon with coir fibre (ACF) as waste materials and an environmentally friendly binder to stabilise lateritic subgrade soil. Experiments, including the one-dimensional consolidation and unconfined compressive strength (UCS) tests, have been conducted to investigate the geotechnical properties of stabilised soil in various percentages of additives 3%, 6%, 9%, and 12% lime and 1%, 2%, and 3% ACF. The results demonstrate that 3% ACF and 12% lime can significantly improve the strength parameters and decrease the void ratio and permeability in the stabilised soil. Furthermore, microstructural analysis was performed before and after stabilisation for optimum content. The microstructural analysis proves that AC and lime particles fill soil voids, and gel formation binds the soil particles in the stabilised soil matrix. The results show that 3% ACF stabilised soil is comparable with 12% lime in UCS value and decreasing void ratio. Furthermore, both are suitable for subgrade of low-volume road stability according to Malaysian standards.